Chapter The development of "sustainable" surveillance and monitoring activity carried out by the italian Coast guard for the safeguard of the Marine Protected Areas - Altavilla, Santo (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The Italian Coast Guard is responsible of surveillance of the Marine Protected Areas and also fulfills essential maritime environmental police tasks in order to protect the maritime and coastal environment. Over the years, specific environmental maritime police campaigns and joint operations have been carried out with the aim of combining the protection of the maritime environment, the safeguard of coasts and biological resources, which are closely connected with each other, through the use of the assets and ITCG specialized units able to discover, analyze and repress environmental offences.